2011
DOI: 10.1039/c1cc11615k
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic nanostructured silicon surfaces with controllable broadband reflectance

Abstract: Nanostructured superhydrophobic silicon surfaces with tunable reflectance are fabricated via a simple maskless deep reactive-ion etching process. By controlling the scale of the high-aspect-ratio nanostructures on a wafer-scale surface, surface reflectance is maximized or minimized over the UV-vis-IR range while maintaining superhydrophobic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 25 publications
0
41
0
1
Order By: Relevance
“…[ 20 ] However, achieving well-defi ned, tunable textures with feature sizes less than 100 nm using these methods remains challenging. Block-copolymer-based thin-fi lm patterning [24][25][26][27] can provide a potential solution because of its high spatial resolution and large area (>cm 2 ) throughput.…”
Section: Doi: 101002/adma201304006mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 20 ] However, achieving well-defi ned, tunable textures with feature sizes less than 100 nm using these methods remains challenging. Block-copolymer-based thin-fi lm patterning [24][25][26][27] can provide a potential solution because of its high spatial resolution and large area (>cm 2 ) throughput.…”
Section: Doi: 101002/adma201304006mentioning
confidence: 99%
“…[ 17,18 ] Indeed, previous studies have shown that nanoscale features alone can achieve similar static contact angles and contact angle hysteresis compared with hierarchical surfaces. [19][20][21] In particular, surfaces textured at the sub-100 nm length scale may achieve the robustness required for applications such as automotive and aircraft windshields, and steam turbine power generators, where fl uids are subjected to high pressures or when droplets impact solid surfaces at speeds in excess of 10 m s −1 . They may also enable integration of SH coatings with antifouling and low fl ow-resistance into nanofl uidic devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several methods have been reported to grow Si-NWs vertically, viz., chemical vapor deposition (CVD), nanoparticles-assisted etching, reactive-ion etching (RIE), etc. (Yi et al 2011;Krylyuk et al 2010;Moutanabbir et al 2011;Shin and Filler 2012;Zhong et al 2011;Chen et al 2010;Huang et al 2008;Geyer et al 2012;Yuan et al 2012;Chang et al 2012;Cho et al 2011;Sainiemi et al 2011;Garnett and Yang 2010;Zhu et al 2009). The SiNWs prepared by these methods exhibit promising photoelectron conversion characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic surfaces with a high water contact angle (WCA) of >150° and a low sliding angle (<10°) provide very attractive functionalities for many applications [1][2][3][4], such as self-cleaning, anti-icing, and drag-reduction coatings. The contact angle of the hydrophobic surface depends on the surface chemistry and roughness of the surface.…”
Section: Introductionmentioning
confidence: 99%